The Photobiology of Heterosigma akashiwo. Photoacclimation, Diurnal Periodicity, and its Ability to Rapidly Exploit Exposure to High Light. Issue 2 (25th February 2013) - Hennige, Sebastian J.; Coyne, Kathryn J.; MacIntyre, Hugh; Liefer, Justin; Warner, Mark E.
<x xml:space="preserve">Abstract</x> Periodic and seasonal exposure to high light is a common occurrence for many near‐shore and estuarine phytoplankton. Rapid acclimatization to shifts in light may provide an axis by which some species of phytoplankton can outcompete other microalgae. Patterns of photoacclimation and photosynthetic capacity in the raphidophyte Heterosigma akashiwo (Hada) Hada ex Hara et Chihara isolated from the mid‐Atlantic of the United States were followed in continuous cultures at low‐ and high‐light intensities, followed by reciprocal shifts to the opposite light level. The maximum quantum yield (Fv/Fm) as well as the photosynthetic cross‐section (σPSII) of photosystem II was higher in high‐light cultures compared to low‐light cultures. Significant diurnal variability in photochemistry and photoprotection was noted at both light levels, and high‐light‐acclimated cultures displayed greater variability in photoprotective pathways. When shifted from low to high light, there was only a slight and temporary decline in maximum quantum yield, while cell specific growth more than doubled within 24 h. Rapid acclimation to high light was facilitated by short‐term photoprotection (nonphotochemical quenching), reduced PSII reaction center connectivity, and electron transport. Short‐term increases in de‐epoxidated xanthophyll pigments contributed to nonphotochemical protection, but lagged behind initial increases in nonphotochemical quenching and were not the primary pathway of photoprotection in this alga. By 48 h, photochemistry of cultures shifted from low to high light resembled long‐term high‐light‐acclimated cultures. This isolate of H. akashiwo appears well poised to exploit rapid shifts in light by using unique cellular adjustments in light harvesting and photochemistry.